Sedimentary Facies of Seblat Formation Semaka Districts, Lampung, Indonesia - Evan Rosyadi Ogara (Journal of Science and Applicative Technology, 2021)
Seblat Formation had been exposed in Sedayu village, Lampung. Stratigraphic measurements and detailed description at several outcrops was performed on Seblat Formation. The facies of Seblat Formation base on sedimentological study can be divided into to two facies, classical turbidtes and slump. Classical turbidites in study area characterized by monotonous sandstone intercalated with mudstone and slump facies consist of mudstone and fine-grained sandstone with total thickness around 5 meters and the thickness of each layer ranges from 3-13 centimeters. Based on two sedimentary facies, mid fan (smooth-channelled) and inner fan is proposed for Seblat Formation.